Saturation of trapped particle instability induced by vortex-merging in electron plasma waves. (24th July 2020) - Yang, T; Feng, Q S; Wang, Y X; Zhou, Y Z; Ban, S S; Zhang, S T; Xie, R; Jiang, Y; Cao, L H; Liu, Z J; Zheng, C Y
Abstract: Phase space vortex merging in electron plasma waves is researched by applying a periodically changing electric field in plasma space with Maxwellian velocity distribution. The pump electric field excites the electron plasma wave with large amplitude and electron phase space vortices are formed. The electron plasma wave can be transited to longer wave modes through vortex merging processes. Excepting the fundamental mode of electron plasma waves, two or more modes appear and grow exponentially before vortex merging. After merging, another mode replaces the initial pumping wave as the strongest wave mode. It is verified that the growth of this new strong mode is related to trapping particle instability. Vortex merging is one of the saturation mechanisms of trapped particle instability.